Food Resilience Strategy Based on Local Wisdom in Deli Serdang Regency - Rizka Amalia Lubis; Yusrizal; Rahmi Syahriza; Maryam Batubara (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to discover how the primary priority strategy for local wisdom-based food security can be found in Deli Serdang by presenting the internal and external conditions that have been carried out so far. Additionally, the researcher also outlines some urgent measures that need to be implemented to better direct the local wisdom-based food security strategy. The method used is qualitative, employing SWOT analysis and QSPM. The number of respondents who filled out the questionnaire consisted of 5 respondents each from farmers, local communities, as well as traditional and religious figures, and 5 respondents from expert professionals. Based on the SWOT analysis, the strategy quadrant obtained after being processed in the IFE and EFE matrices falls under Quadrant I. This indicates that the strategy used is a progressive strategy. This strategy implies that local wisdom-based food security in Deli Serdang possesses strength and potential. Furthermore, the QSPM analysis yielded the result that the primary priority strategy to be pursued is to focus on preserving local wisdom-based food security to turn it into an international-scale business opportunity.